The Role of Social Workers in Improving the Physical Health of People Who Use Mental Health Services. Issue 4 (1st October 2020) - Maylea, Chris; Roberts, Russell; Craik, Christine
ABSTRACT: This paper highlights some key actions social workers can take to help improve the physical health of people living with mental illness. Despite an 80% comorbidity rate, many people living with mental illness still do not receive a physical health check-up. For this and other reasons, people living with mental illness die, on average, 10–20 years prematurely. This early death is usually preceded by years or decades of poor health. Using a collective impact approach, this paper discusses actions to increase autonomy, advocate for better access to quality physical health care, and minimise iatrogenic harm for people living with mental illness. IMPLICATIONS This paper highlights the key opportunities for social workers to improve the physical health of people living with mental illness. Using a collective impact approach, it highlights the vital role social workers can play in enacting the essential elements of the Equally Well national consensus statement, such as advocating equity of access to physical health care services, supporting quality care, and reducing stigma and discrimination for people living with mental illness.